DIVERGENT PARADIGMS: A COMPARATIVE APPRAISAL OF OPERATIONAL MECHANICS AND RISK-SHARING IN ISLAMIC AND CONVENTIONAL BANKING (Al-Aasar, 2026)
This study provides a comprehensive comparative appraisal of the operational principles and risk-sharing paradigms within Islamic and conventional banking systems. Moving beyond theoretical descriptions, the research evaluates the systemic divergences between debt-based and equity-based intermediation, focusing on fiduciary stewardship, $Riba$-free capital usage, and Shari’ah-compliant governance. A specific focus is placed on the Pakistani dual-banking sector to analyze the gap between theoretical ideals and market realities. The findings reveal that while functional convergence is appearing in areas of Corporate Social Responsibility (CSR), profound systemic gaps remain in risk management and asset-liability parity. This research concludes that the Islamic model offers a resilient, asset-backed alternative to conventional debt-centricity. It proposes a "Collaborative Paradigm" integrating ethical risk-sharing with modern financial infrastructure  as a blueprint for financial innovation and stability in emerging global markets.